A Comparative Study on the Etfects of 『Palmisoyo-San gamibang』, 『Gyebu-Tang』 and 『Boganyangje』 on the Thyrotoxicosis of Rats - Yeun-Seong Lee; Kyeong-Sun Soh; Chan-Gil Jeong (Korean Pharmacopuncture Institute, 2005)
In order to study comparatively the effects of 「Palmisoyo-San gamibang(八味逍遙散加味方)」(AP), 「Gyebu-Tang(계부탕(桂附湯))」(GT) and 「Boganyangje(補肝陽劑)」(BG) on the thyrotoxicosis rats, we have made thyrotoxicosis rat model by administration sodium levothyroxine p.o. during 4 days(Control group), and have administered solid extract of AP(236.8mg/200g/day : Sample Igroup), GT(80mg/200g/day : Sample II group) and BG(70.4mg/200g/day : Sample III group) p.o. to thyrotoxicosis rats during 3 days from 3rd day. We measured the body weight(BW), body temperature(BT), levels of Serum T3 · T4 · free T3 · free T4 and TSH after administrating solid extract of AP, GT and BG. 1. Sample I group showed significantly high increasing rate compared with Control, Sample II and Sample III group, but it showed significantly lower levels of BT, T4 and free T4 than those of Control, Sample II and Sample III group. 2. We could know that AP suppress the alteration of T4 to T3. 3. Sample II and Sample III group showed opposite results to Sample I group in the BW., BT, T4 and free T4. Especially Sample III was significantly higher than Control, Sample I and Sample II, so we could guess that BG stimulates the formation of thyroid hormones. According to the above experimental results, 「Palmisoyo-San gamibang(八味逍遙散加味方)」is assumed to have a curative effect against the thyrotoxicosis rat induced by sodium levothyroxine, and to suppress the alteration of T4 to T3. And we can suppose that 「Boganyangje(補肝陽劑)」has a curative effect against the hypothyroidism.